A qualitative research on career expectations of civilian nurses in military hospitals (军队医院文职护理人员职业期待的质性研究) - CAI Aini (蔡爱旎); HONG Hanhan (洪涵涵); LU Jiaojiao (卢姣姣); JI Dandan (季丹丹); SHANG Yanjun (尚彦君) (中西医结合护理)
Objective To investigate the true career expectations of civilian nurses in military hospitals, so as to provide reference for relevant administrators to formulate plans of human resource management and career development. Methods A semi-structured in-depth interview was conducted with 14 civilian nurses from three military hospitals by using phenomenological method of qualitative research, and Colaizzi 7-step method was implemented for data analysis and data synthesis. Results Through a process of analysis, four themes representing nurses’ career expectations were created: Need for medical support; Expanding career development; Changes in pressure and challenge; Improvement of welfare benefits. Conclusion Relevant administrators should have a deep understanding of career needs and expectations of civilian nurses in military hospitals, and enhance their sense of mission by addressing existing problems. (目的 了解军队医院文职护理人员对职业的真实期待, 以期为相关军队医院管理部门制定更准确的人力资源管理和职业发展规划提供依据。方法 采用质性研究方法, 对上海3所军队医院的14名文职护理人员进行半结构式访谈, 并运用 Colaizzi七步分析法, 对访谈资料进行分析、整理、总结, 提炼出主题。结果 通过访谈归纳出4个主题: 卫勤保障的需求; 拓展职业发展空间; 压力和挑战的改变; 提升福利待遇标准; 结论 管理者应深入了解并重视文职护理人员的职业需求和期待, 针对性解决存在的问题, 使其更好地履行使命。)